Armenian Amulet Scrolls in Collections of Paris - Ghazaryan, Davit (Matenadaran, 2024)
Abstract This paper describes the Armenian amulet scrolls kept in the Bibliothèque nationale de France (BnF) and in the private collection of Garig and Varvara Basmadjians in Paris. It is based on the author’s research carried out in 2016, when he was a recipient of the “Sirarpie Der-Nersessian Association” scholarship. Before listing and describing those items, the author refers to the etymology of the word hmayil (“amulet scroll”), mentions the other Armenian names of amulet scrolls, provides general information on what they are, lists the most important libraries where those scrolls are kept, and classifies the miniatures (of the fifteenth–nineteenth centuries) found in them into 5 groups.
Keywords: Saint Cyprian